Autonomic cardiac regulation, blood pressure and cardiorespiratory fitness responses to different training doses over a 12 week group program in the elderly. (May 2017) - McKune, A.J.; Peters, B.; Ramklass, S.S.; van Heerden, J.; Roberts, C.; Krejčí, J.; Botek, M.
Highlights: Blood pressure and 6-min walk improved irrespective of training frequency in elderly. Heart rate variability (HRV) decreased when training three sessions/week. HRV was maintained when training twice a week. Abstract: Aim: The study assessed the effects of different weekly training frequencies performed over a 12 week exercise programme (strength, endurance, balance) on autonomic cardiac activity, blood pressure and cardiorespiratory fitness (CRF) in elderly individuals. Methods: Fifty-eight individuals participated in the study: 2TG (N = 24, 71.1 ± 6.4 yrs; 19 females, 5 males) performing two, 60 min sessions/week; and 3TG (N = 34, 72.3 ± 7.9 yrs; 25 females, 9 males) performing three, 60 min sessions/week. Time domain and spectral analysis of heart rate variability (HRV) quantified autonomic cardiac regulation. Results: Natural logarithm (Ln) transformation was applied to all HRV parameters. There were significant reductions in total power (Ln TP) (p = 0.006), low frequency (Ln LF) (p = 0.013), high frequency (Ln HF) (p = 0.013) and root mean square of successive differences (Ln rMSSD) (p = 0.014) post training in 3TG after intervention. Diastolic BP (DBP) decreased significantly in both groups (2TG: P < 0.001; 3TG: P < 0.001). Both groups showed significant improvements in six-minute walk distance (2TG: P = 0.003, 3TG: P = 0.001). However, there were significant HRV differences between 2TG and 3TG for Ln TP (P = 0.018), Ln LF (P = 0.049), Ln HF (P = 0.039) and Ln rMSSD (P = 0.049). Conclusions: A combined exercise programme resulted in improved DBP and CRF irrespective of training two or three 60 min sessions/week. However, training three, sessions/week induced negative health-related changes in autonomic cardiac activity through reducing HRV parasympathetic function, while HRV was maintained in the group training twice a week.